2007
DOI: 10.1007/s00280-007-0462-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of selected non-steroidal anti-inflammatory drugs and their derivatives against cancer cells in vitro

Abstract: The method of chemotherapy (i.e., intravascular, intrathecal, oral) might dictate the choice of NSAID/NSAID derivative used to treat/prevent a given type of cancer. Also, the p75 NTR tumor suppressor appears to be a common molecular mechanism that mediates the growth inhibiting effectiveness of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 51 publications
1
46
1
Order By: Relevance
“…In nested case-control study Daugherty et al [34] observed that risks of prostate cancer were significantly reduced among regular ibuprofen users who carried allele variants at four non-synonymous single nucleotide polymorphism (nsSNP) loci of the -methylacyl-CoA-racemase (AMACR) gene and carried TGTGCG haplotype. Overexpression of AMACR, which is implicated in the activation of the COX-inhibiting form of ibuprofen, has been commonly observed in prostate cancer subjects [34,38]. Similarly, overexpression of COX-2 and increased prostaglandin biosynthesis correlates with carcinogenesis and metastasis at most anatomic sites [36].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…In nested case-control study Daugherty et al [34] observed that risks of prostate cancer were significantly reduced among regular ibuprofen users who carried allele variants at four non-synonymous single nucleotide polymorphism (nsSNP) loci of the -methylacyl-CoA-racemase (AMACR) gene and carried TGTGCG haplotype. Overexpression of AMACR, which is implicated in the activation of the COX-inhibiting form of ibuprofen, has been commonly observed in prostate cancer subjects [34,38]. Similarly, overexpression of COX-2 and increased prostaglandin biosynthesis correlates with carcinogenesis and metastasis at most anatomic sites [36].…”
Section: Introductionmentioning
confidence: 97%
“…In case of prostate cancer and ovarian cancer lines the up-regulation of the p75 NTR tumor suppressor which appears to be a common molecular mechanism that mediates the growth inhibiting effectiveness of these drugs [34,36,38]. Andrews et al [38] reveals that R-flurbiprofen and R-ibuprofen were most effective at clinically relevant dosages over the nitric oxide-linked aspirin and celecoxib to inhibit the growth of different human cancer cells including cell lines expressing multidrug resistance-1 -glycoprotein (MDR-1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This interest is based on the fact that his R enantiomer has been referred as a promoter of efficient inhibition on the development of varied forms of cancer in human beings [2], such as, the prostate cancer [3][4][5] and the colon cancer [6,7]. The most recent application area of flurbiprofen enantiomers has been described in numerous clinic and pharmacological reports, in which the R enantiomer is referred as an important hypothetical drug used to minimize the progression of Alzheimer disease [8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%